2018
DOI: 10.1002/jsfa.9232
|View full text |Cite
|
Sign up to set email alerts
|

Lipid oxidation stability of ultra‐high‐temperature short‐time sterilization sporoderm‐broken pine pollen (UHT‐PP) and 60Co‐irradiation sterilization sporoderm‐broken pine pollen (60Co‐PP)

Abstract: Rancidity occurs more readily in UHT-PP than in R-PP and Co-PP during storage, probably because significant lipid oxidation and antioxidant degradation occurred during the UHT sterilization sporoderm-broken processing of pine pollen. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…proved that irradiation sterilization could effectively kill 90% bacteria (Shen et al, 1997). In addition, Shan et al (2019) studied the lipid oxidation stability of ultra-high-temperature short-time sterilization sporoderm-broken pine pollen (UHT-PP) and 60 Co irradiation sterilized broken pine pollen, and found that UHT-PP was more prone to rancidity, which might be due to the significant lipid oxidation and antioxidant degradation of the process. Also, total phenolic content and total flavonoid content were increased by 16.90% and 14.66% in soluble phenolics, and decreased by 53.26% and 21.57% in insoluble bound phenolic after 60 Co-irradiation (Cheng, Quan, et al, 2020).…”
mentioning
confidence: 99%
“…proved that irradiation sterilization could effectively kill 90% bacteria (Shen et al, 1997). In addition, Shan et al (2019) studied the lipid oxidation stability of ultra-high-temperature short-time sterilization sporoderm-broken pine pollen (UHT-PP) and 60 Co irradiation sterilized broken pine pollen, and found that UHT-PP was more prone to rancidity, which might be due to the significant lipid oxidation and antioxidant degradation of the process. Also, total phenolic content and total flavonoid content were increased by 16.90% and 14.66% in soluble phenolics, and decreased by 53.26% and 21.57% in insoluble bound phenolic after 60 Co-irradiation (Cheng, Quan, et al, 2020).…”
mentioning
confidence: 99%
“…The most abundant fatty acids measured in the pine pollen samples were palmitic acid (23.42-28.60%), oleic acids (34.8%-42.6%) and linoleic acids(15.9%-26.4%),which was in general agreement with that reported in the literature. [4] Total unsaturated acids (UFA) ranged from 61.1% to 68.7%, in which monounsaturated acids (MUFA) and polyunsaturated acids (PUFA) changed from 35.7% to 43.5% and 17.6% to 29.5%, respectively. High proportions of unsaturated acids, especially oleic and linoleic acids, were probably one of the most important factors influencing lipid peroxidation, resulting in the formation of aliphatic aldehydes, ketones, alcohols, furans and acids.…”
Section: Electron-beam and Thermal Sterilization On Fatty Acids In Pine Pollenmentioning
confidence: 99%
“…Therefore, we speculated that the unsaturated fatty acid that mainly causes the odor of pine pollen during processing was linoleic acid. [4] Table 4. Fatty acid compositions (%) of pine pollen samples.…”
Section: Electron-beam and Thermal Sterilization On Fatty Acids In Pine Pollenmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen, the male germ cell, is the ‘source of life’ of a plant (Campos et al ., 2008) and also the prime nutrient resource for development of bees (Shan et al ., 2019). Pollen is considered a functional food supplement for its richness of proteins, amino acids, carbohydrates and micronutrients and is reported to have antioxidant, antimicrobial, antimutagenic, anti‐inflammatory, antiallergic and anticarcinogenic properties, as well as therapeutic functions (Carpe et al ., 2009; Pascoal et al ., 2014; Li et al ., 2018b).…”
Section: Introductionmentioning
confidence: 99%